Evaluation of Grouting Effectiveness on Cracks in Cement-Stabilized Macadam Layer Based on Pavement Mechanical Response Using FBG Sensors - Min Zhang; Hongbin Hu; Cheng Ren; Zekun Shang; Xianyong Ma (Applied Sciences)
Cracking in semi-rigid cement-stabilized macadam bases constitutes a prevalent distress in asphalt pavements. While extensive research exists on grouting materials for crack rehabilitation, quantitative assessment methodologies for treatment efficacy remain underdeveloped. This study proposes a novel evaluation framework integrating fiber Bragg grating (FBG) technology to monitor pavement mechanical responses under traffic loads. Conducted on the South China Expressway project, the methodology encompassed (1) a method for back-calculating the modulus of the asphalt layer based on Hooke’s Law; (2) a sensor layout plan with FBG sensors buried at the top of the pavement base in seven sections; (3) statistical analysis of the asphalt modulus based on the mechanical response when a large number of vehicles passed; and (4) comparative analysis of modulus variations to establish quantitative performance metrics. The results demonstrate that high-strength geopolymer materials significantly enhanced the elastic modulus of the asphalt concrete layer, achieving 34% improvement without a waterproofing agent versus 19% with a waterproofing agent. Polymer-treated sections exhibited a mean elastic modulus of 676.15 MPa, substantially exceeding untreated pavement performance. Low-strength geopolymers showed marginal improvements. The modulus hierarchy was as follows: high-strength geopolymer (without waterproofing agent) > polymer > high-strength geopolymer (with waterproofing agent) > low-strength geopolymer (without waterproofing agent) > low-strength geopolymer (with waterproofing agent) > intact pavement > untreated pavement. These findings demonstrate that a high-strength geopolymer without a waterproofing agent and high-polymer materials constitute optimal grouting materials for this project. The developed methodology provides critical insights for grout material selection, construction process optimization, and post-treatment maintenance strategies, advancing quality control protocols in pavement rehabilitation engineering.